2013
DOI: 10.1103/physrevb.87.235111
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity under pressure inRFeAsO1xFx(et al.

Abstract: Superconducting transition under pressure (P ) has been investigated for optimum-doped RFeAsO 1−x F x (R = La, Ce-Sm) by dc magnetization measurements. For R = La, T c is found to be pressure independent up to P ∼ 3.0 GPa and then shows a monotonic decrease with increasing pressure. The plateau width decreases for the system with smaller lattice constants and shrinks to almost zero for R = Sm. From the T c (P ) data, we construct the T c evolution map on the height of the As atom from the Fe-plane h As versus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Interestingly, near optimal doping, in both 122 and 1111 families, there is indeed a straightforward connection between the structural parameters and T c . 32,33 Near optimal doping, d wave is known to be a subdominant superconducting state while s wave is the dominant one. 34 The Loss of this straightforward connection between superconductivity and structural parameters in the over-doped regime could in fact result from a dominant d wave state.…”
Section: Table I Lattice Parameters (A and C) Unit Cell Volume (V = Camentioning
confidence: 99%
“…Interestingly, near optimal doping, in both 122 and 1111 families, there is indeed a straightforward connection between the structural parameters and T c . 32,33 Near optimal doping, d wave is known to be a subdominant superconducting state while s wave is the dominant one. 34 The Loss of this straightforward connection between superconductivity and structural parameters in the over-doped regime could in fact result from a dominant d wave state.…”
Section: Table I Lattice Parameters (A and C) Unit Cell Volume (V = Camentioning
confidence: 99%
“…In pressure dependent ρ ( T ) measurements, usually the superconducting transition is broadened and T c has been mainly determined from the onset of resistive drop 1116,1823 . In contrast, measurements of magnetic susceptibility on Ln FeAsO 1− x F x compounds as a function of applied pressure has revealed that T c is independent up to a threshold value of pressure and then decreases with further increase in pressure 24 .…”
Section: Introductionmentioning
confidence: 90%
“…Miyoshi et al . 24 measured magnetic susceptibility on Ln FeAsO 1− x F x compounds and claimed that T c is insensitive up to a threshold value of pressure and then decreases with further increase in pressure. For PrFeAsO 1− x F x , it seems that T c does not change from its ambient pressure value 43 K up to about 1 GPa and then decreases with the increase in pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the charge doping, achieved by means of O 1−x F x or Fe 1−x Co x chemical * Corresponding author: roberto.derenzi@unipr.it substitutions, external pressure is also known to lead to a superconducting ground state in RFeAsO, even for undoped compounds (see [13] and references therein). In this respect, it should be stressed that the chemical substitution of R ions also shrinks the lattice and sizeably affects crystallographic properties like the tetrahedral angle and the pnictogen height, two quantities which are strictly correlated with the value of the superconducting transition temperature T c [14]. Accordingly, only small R ions like Sm allow to obtain the maximum T c value of ∼ 55 K -incidentally, the highest value known up to now for pnictide materials [15,16,17].…”
Section: Introductionmentioning
confidence: 99%